2016
DOI: 10.1177/0960327116680275
|View full text |Cite
|
Sign up to set email alerts
|

S-Allyl cysteine alleviates inflammation by modulating the expression of NF-κB during chromium (VI)-induced hepatotoxicity in rats

Abstract: Hexavalent chromium (Cr (VI)) is a common environmental pollutant. Cr (VI) exposure can lead to severe damage to the liver, but the preventive measures to diminish Cr (VI)-induced hepatotoxicity need further study. S-allyl cysteine (SAC) is a constituent of garlic ( Allium sativum) and has many beneficial effects to humans and rodents. In this study, we intended to analyze the mechanistic role of SAC during Cr (VI)-induced hepatotoxicity. Male Wistar albino rats were induced with 17 mg/kg body weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 59 publications
0
27
0
Order By: Relevance
“…To support our findings, it has been proved that a fraction of protective property of SAC during chromiuminduced hepatotoxicity is attributable to its inhibition of inflammation, partly mediated via modulating the expression of NF-κB in rats. [22] Additionally, SAC could reduce mucosal damage of the stomach due to non-steroidal anti-inflammatory drugs via inhibition of Cox 2 and exerting an anti-inflammatory effect. [64] Besides, it has shown that SAC downregulates TLR4 and NF-κB in LPS-induced model of acute kidney injury [23] and in this way has exerted its protective effect in this study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…To support our findings, it has been proved that a fraction of protective property of SAC during chromiuminduced hepatotoxicity is attributable to its inhibition of inflammation, partly mediated via modulating the expression of NF-κB in rats. [22] Additionally, SAC could reduce mucosal damage of the stomach due to non-steroidal anti-inflammatory drugs via inhibition of Cox 2 and exerting an anti-inflammatory effect. [64] Besides, it has shown that SAC downregulates TLR4 and NF-κB in LPS-induced model of acute kidney injury [23] and in this way has exerted its protective effect in this study.…”
Section: Discussionmentioning
confidence: 99%
“…[30,31] Animals in treatment groups were administered SAC (Sigma-Aldrich) per os using a gavage needle at mentioned doses (25 or 100 mg/kg/d) for 3 days till 1 hour before LPS/D-Gal challenge. SAC dose was taken from previous studies on its anti-inflammatory and defensive effects against hepatotoxicity due to chromium in rats [22] and its mitigation of oxidative injury and improvement of neurologic deficits in an animal model of focal cerebral ischemia. [32] In addition, renoprotective effect of oral SAC at doses of 25, 50 and 100 mg/kg has been evaluated in the LPS-induced model of acute kidney injury in the C57BL/6 mouse and SAC at a dose of 100 mg/kg was most effective.…”
Section: Experimental Scheme Of the Studymentioning
confidence: 99%
See 2 more Smart Citations
“…ascribed, at least in part, to the anti-inflammatory (9,11) and/or antioxidant (12,13) activities of sulfur compounds in AGE.…”
Section: Sulfur-containing Amino Acids In Aged Garlic Extract Inhibitmentioning
confidence: 99%